Faktor Kecemasan Tenaga Kesehatan dalam Memberikan Perawatan pada Pasien Covid-19: A Literatur Review - Hermanto Hermanto; Putria Carolina; Siti Santy Sianipar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Covid-19 as a global pandemic has overwhelmed the global health care system, and medical personnel experience a large workload due to long service shifts, which impact psychological disorders, one of which is anxiety; the anxiety experienced varies from mild, moderate to severe. To find out and display the causes of anxiety that arise in health workers while dealing with COVID-19 patients through searching literature articles. This research method is a literature review, with article searches starting from 2019-2020, using the ProQuest, PubMed, sciencedirect.com, google scholar, and crossref databases with the keywords health workers anxiety, OR Nurse anxiety, OR covid-19 patients. The identification of articles found as many as 620 articles and included in the selection criteria for 101 articles. 101 articles were included in the inclusion criteria selection, 11 articles were found that met the inclusion criteria. 11 articles were extracted and found several factors including gender, age, education, marital status, availability of APD, fear of infection, presence of comorbidities, having elderly family members, working conditions and environment, direct contact, type of hospital, profession, history of anxiety, patient honesty. The factors that cause anxiety in health workers when treating COVID-19 patients occur from individual internal and external factors. It occurs from individual internal factors including gender, age, education, marital status, fear of being infected, the presence of comorbidities, having a history of anxiety. External factors include the availability of APD, having elderly family members, working conditions and environment, direct contact, type of hospital, profession, patient honesty.